J-shaped association between dietary thiamine intake and the risk of cognitive decline in cognitively healthy, older Chinese individuals - Yuanyuan Zhang; Xianhui Qin; Chengzhang Liu; Chun Zhou; Mengyi Liu; Panpan He; Ziliang Ye; Qiguo Meng; Yuanxiu Wei; Xinyue Su (General Psychiatry)
Background The prospective association of dietary thiamine intake with the risk of cognitive decline among the general older adults remains uncertain.Aims To investigate the association between dietary thiamine intake and cognitive decline in cognitively healthy, older Chinese individuals.Methods The study included a total of 3106 participants capable of completing repeated cognitive function tests. Dietary nutrient intake information was collected through 3-day dietary recalls and using a 3-day food-weighed method to assess cooking oil and condiment consumption. Cognitive decline was defined as the 5-year decline rate in global or composite cognitive scores based on a subset of items from the Telephone Interview for Cognitive Status–modiﬁed.Results The median follow-up duration was 5.9 years. There was a J-shaped relationship between dietary thiamine intake and the 5-year decline rate in global and composite cognitive scores, with an inflection point of 0.68 mg/day (95% confidence interval (CI): 0.56 to 0.80) and a minimal risk at 0.60–1.00 mg/day of dietary thiamine intake. Before the inflection point, thiamine intake was not significantly associated with cognitive decline. Beyond the inflection point, each unit increase in thiamine intake (mg/day) was associated with a significant decrease of 4.24 (95% CI: 2.22 to 6.27) points in the global score and 0.49 (95% CI: 0.23 to 0.76) standard units in the composite score within 5 years. A stronger positive association between thiamine intake and cognitive decline was observed in those with hypertension, obesity and those who were non-smokers (all p<0.05).Conclusions This study revealed a J-shaped association between dietary thiamine intake and cognitive decline in cognitively healthy, older Chinese individuals, with an inflection point at 0.68 mg/day and a minimal risk at 0.60–1.00 mg/day of dietary thiamine intake.